Hubungan Tingkat Dukungan Keluarga, Pengetahuan Keluarga dan Peran Kader Terhadap Kunjungan Balita Ke Posyandu Tahun 2023 - Mardiana, Ommy; Madjid, Syarah; Rumbawa, Imela; Idham, Jamila (Lembaga Publikasi Ilmiah Nusantara, 2024)
Indonesia still faces nutritional problems, one of which is undernutrition. Undernutrition is a nutritional issue that can affect toddlers. Toddlers, defined as children aged 0–59 months, need close monitoring of their growth and development since they are in the